Changes in phytochemical compounds and antioxidant potential of fresh, frozen, and processed figs (Ficus carica L.) - Petkova, N. (2021)
The aim of the present work was to evaluate some phytochemical compounds in fresh, frozen, and processed yellow-coloured figs (Ficus carica L.). The moisture content, ash, titrable acidity, total chlorophylls, total carotenoids, total phenols, total flavonoids, total anthocyanins, as well as carbohydrates (fructose, glucose, and sucrose) were evaluated. In addition, the antioxidant capacities of fresh, frozen, and processed figs (jam) were determined by DPPH and FRAP assays. The highest values of bioactive compounds and antioxidant activity were found in fresh fruits, while in frozen fruits their levels decreased significantly. The preparation of fig jam was a better approach for preserving some bioactive compounds, especially carotenoids and phenolic compounds. After four months of storage at -18°C, it was observed that there were significant losses in the antioxidant potential, decrease in sucrose content, as well as total phenols, total flavonoids, and total anthocyanins values. In spite of the reduction in some valuable compounds, jam processing retained good amount of them during storage in comparison with freezing storage.